Refocusing the Use of Psychiatric Drugs for Treatment of Gastrointestinal Cancers - Avendaño-Félix, Mariana; Aguilar-Medina, Maribel; Bermudez, Mercedes; Lizárraga-Verdugo, Erik; López-Camarillo, César; Ramos-Payán, Rosalío (Frontiers in Oncology, 2020)
Gastrointestinal cancers (GICs) are the most common human tumors worldwide. Treatments have limited effects and increasing global cancer burden make it necessary to investigate alternative strategies such as drug repurposing. Interestingly, it has been found that psychiatric drugs (PDs) are promising as a new generation of cancer chemotherapies due to their anti-neoplastic properties. This review compiles the state of the art about how PDs have been redirected for cancer therapeutics in GICs. PDs, especially anti-psychotics, anti-depressants and anti-epileptic drugs, have shown effects on cell viability, cell growth, inhibition of proliferation (cell cycle arrest), apoptosis promotion by caspases activation or cytochrome C release, production of ROS and nuclear fragmentation over esophageal, gastric, colorectal, liver and pancreatic cancers. Additionally, PDs can inhibit neovascularization, invasion and metastasis and effects are dose-dependent. Moreover, they can induce chemosensibilization to 5-fluorouracil, gemcitabine and cisplatin and can act synergistically with anti-neoplastic drugs such as gemcitabine. All anti-cancer activities are given by activation or inhibition of pathways such as HDAC1/PTEN/Akt, EGFR/ErbB2/ErbB3 and PI3K/Akt; PI3K-AK-mTOR, HDAC1/PTEN/Akt; Wnt/β-catenin. Further investigations and clinical trials are needed to elucidate all molecular mechanisms involved on anticancer activities as well as adverse effects on patients.